Characteristics of live animal allometric measurements associated with body fat in fat-tailed sheep - Ermias, E.; Rege, J.E.O. (Elsevier, 2003)
Body weight (LW), condition score (BCS), tail length on inner side of tail (TL), tail volume measured by water displacement (TV) and tail circumference (TC), width (TW) as well as thickness at the base (TT) were measured in live Menz (n=303) and Horro (n=151) sheep to determine their possible use in breeding programmes aimed at improving ability to deposit fat in these breeds. The sheep were individually fed for about 3.5 months before slaughter at about 17 months of age. LW at slaughter ranged from 14.5 to 37 kg in the Horro and 16 to 35 kg in the Menz, and was not significantly (P>0.05) different between the two breeds. The fat tail was longer, but thinner and narrower at the base (P<0.01) in the Horro than in the Menz. The combined weight of dissected tail and rump fat (DTRF) was similar in the two breeds (P>0.05). However, the Menz deposited significantly (P<0.01) more fat in other depots. TV explained about 60%, in the Menz, and 58%, in the Horro, of the total variation in DTRF. Multiple regression equation comprising LW and TW explained about 64% of the variation in DTRF in the Menz (R.S.D.=130.4 g). TW, LW and BCS in a multiple regression equation explained about 65% of total ether-extracted body fat (TotEE) in the Menz. However, the precision of estimation of TotEE was marginal in the Horro (R250%). Heritability estimates for LW, TT, TL and TV ranged from 0.37 to 0.54, while estimates for BCS, TW and TC were less than 0.25. Genetic correlations of live animal tail measurements with DTRF were strong and positive (0.69–0.89). Genetic correlations of TL and TT with average daily weight gain (ADG) and efficiency of feed utilisation for weight gain (EFU) during individual feeding period were favourable. Genetic correlation of TC with EFU was also favourable. Genetic correlations of TV with production traits were non-significant due to disproportionately large standard errors. The results suggest that TV is promising for inclusion in selection indices aimed at improving the ability to deposit tail and rump fat and, hence, adaptation to periodic fluctuation of feed supply, in Menz and Horro sheep. However, it is recommended that genetic associations of TV with production traits be verified using larger data sets.